The Evolution of Digital Reading Research: A Bibliometric Analysis Attention, Engagement, Literacy and Learning Outcomes - Jennifer P. Solis (Future Science / FSH-PH Publications, 2026)
The rapid integration of digital technology in education has transformed students on how to read, access information, and engage with learning. While online text, multimedia resources, and interactive learning platforms has become essential to education practice, digital reading progress as a significant area of inquiry. Even though it is a growing importance, the intellectual advancement and thematic structure of the field remain disintegrated. This study investigated the evolution of digital reading research utilizing bibliometric analysis of 562 English-language publications indexed in Scopus from 1992 to 2025. The publications were retrieved using search key related to digital reading, education, attention, engagement, comprehension and learning outcomes. Publication trend analysis, bibliographic coupling and co-word analysis were performed using VOSviewer. The findings revealed a marked increase in research output, particularly in 2020, presenting the expanding role of digital learning environments in education. Bibliographic coupling recognized five major search streams: digital reading engagement and self-regulation, technology-enhanced comprehension, online reading literacy and information evaluation, screen-versus-print reading, and reading modality with digital distractions. Co-word analysis showed four thematic domains covering technology-mediated learning, cognitive and behavioral mechanisms, digital literacy and strategic reading, and online reading comprehension within the New Literacies framework. Generally, the findings specified that digital reading research has advanced beyond print-versus-screen comparisons toward a broader emphasis on digital literacy, self-regulated learning, attention management, and information evaluation.